Genetic, structural, and functional analysis of pathogenic variations causing methylmalonyl-CoA epimerase deficiency - Heuberger, K; Bailey, HJ; Burda, P; Chaikuad, A; Krysztofinska, E; Suormala, T; Bürer, C; Lutz, S; Fowler, B; Froese, DS; Yue, WW; Baumgartner, MR (Elsevier, 2019)
Human methylmalonyl-CoA epimerase (MCEE) catalyzes the interconversion of d-methylmalonyl-CoA and l-methylmalonyl-CoA in propionate catabolism. Autosomal recessive pathogenic variations in MCEE reportedly cause methylmalonic aciduria (MMAuria) in eleven patients. We investigated a cohort of 150 individuals suffering from MMAuria of unknown origin, identifying ten new patients with pathogenic variations in MCEE. Nine patients were homozygous for the known nonsense variation p.Arg47* (c.139C > T), and one for the novel missense variation p.Ile53Arg (c.158T > G). To understand better the molecular basis of MCEE deficiency, we mapped p.Ile53Arg, and two previously described pathogenic variations p.Lys60Gln and p.Arg143Cys, onto our 1.8 Å structure of wild-type (wt) human MCEE. This revealed potential dimeric assembly disruption by p.Ile53Arg, but no clear defects from p.Lys60Gln or p.Arg143Cys. We solved the structure of MCEE-Arg143Cys to 1.9 Å and found significant disruption of two important loop structures, potentially impacting surface features as well as the active-site pocket. Functional analysis of MCEE-Ile53Arg expressed in a bacterial recombinant system as well as patient-derived fibroblasts revealed nearly undetectable soluble protein levels, defective globular protein behavior, and using a newly developed assay, lack of enzymatic activity - consistent with misfolded protein. By contrast, soluble protein levels, unfolding characteristics and activity of MCEE-Lys60Gln were comparable to wt, leaving unclear how this variation may cause disease. MCEE-Arg143Cys was detectable at comparable levels to wt MCEE, but had slightly altered unfolding kinetics and greatly reduced activity. These studies reveal ten new patients with MCEE deficiency and rationalize misfolding and loss of activity as molecular defects in MCEE-type MMAuria.